Becoming a strainer school: schooling dynamics of students with disabilities in the urban poverty contexts in the Metropolitan Region of Buenos Aires (Praxis Educativa, 2020)
In this article we present research results about the dynamics of schooling of students with disabilities in a special education school located in contexts of urban poverty in the Metropolitan Region of Buenos Aires. We describe in a dense way the conditions of schooling, as well as the multiple tasks in which inclusion between the intersection of disability and poverty is effective. The methodological strategy is based on quantitative techniques - from statistical sources - and qualitative ones, specifically in-depth interviews with the teaching staff of this school. Among the main results through the construction of analytical categories, we propose that this school, given the proposed intersection, becomes a strainer school. This has a direct impact on the schooling dynamics of the students and on the subjectivity of the teachers who, daily, struggle to reverse that notion and, far from not being involved, make it a power.
Keywords: disability– urban poverty– school – inclusion – exclusion